2013
DOI: 10.1111/jfpe.12028
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Behavior of Turmeric (Curcuma Longa) under Ambient and Cryogenic Conditions

Abstract: The present study involves the characterization of fracture properties of spice turmeric (Curcuma longa) under ambient and cryogenic conditions (−54C). Material properties needed for fracture mechanism prediction, particle characterization and etheric oil analyses were experimentally determined on turmeric powder produced under ambient and cryogenic processes. The results of stress‐strain behavior of turmeric showed that there was an increased particle strength, modulus of elasticity and maximum stress intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…In the present study, mango peels were dried in hot air oven (40 6 3 8C) prior to Cryo-grinding and SEM analysis revealed the smooth and porous structure of Dashehari and Fazli. Results of present study are in line with Sridhar and Sommer (2013) who found that, Instead of strong interatomic and intermolecular bond, sub-zero temperature favors the deformation of material at slower rate.…”
Section: Surface Morphologysupporting
confidence: 93%
“…In the present study, mango peels were dried in hot air oven (40 6 3 8C) prior to Cryo-grinding and SEM analysis revealed the smooth and porous structure of Dashehari and Fazli. Results of present study are in line with Sridhar and Sommer (2013) who found that, Instead of strong interatomic and intermolecular bond, sub-zero temperature favors the deformation of material at slower rate.…”
Section: Surface Morphologysupporting
confidence: 93%
“…The crack propagation is rapid in the brittle type of fracture while there is very less microdeformation or no gross deformation (Hertzberg ) due to close interatomic and intermolecular bonds. This signifies that under sub‐zero temperature condition, although, the interatomic and intermolecular forces are higher, the material deforms less readily (Sridhar and Sommer ) which could be observed in the SEM micrographs of the surface morphology and microstructure of black pepper sample (Fig. A,B).…”
Section: Resultsmentioning
confidence: 81%
“…The samples were compressed to 3/4th of their original dimension ( D g of 4.90 mm). The samples for sub‐zero temperature condition was prepared by dipping the seeds in LN 2 for a period of 15 min before performing the compression test, and the uniformity of the temperature was assured by achieving complete embrittlement of the sample (below T g ; Sridhar and Sommer ). Temperatures of the samples were measured just before and after the test was performed with the help of a temperature indicator (Testo, Lenzkirch, Germany) with an accuracy of ± 0.01°C, and the difference was found to be ± 3°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations